A 3D isogeometric FE-IBE coupling method for acoustic-structural interaction problems with complex coupling models. (15th December 2020) - Wu, Y.H.; Dong, C.Y.; Yang, H.S.
Abstract: In this paper, Finite Element-Indirect Boundary Element (FE-IBE) coupling approach based on the Isogeometric Analysis (IGA) framework is proposed to deal with Acoustic-Structural Interaction (ASI) problems. Numerical simulation of thin-walled structures is carried out by using isogeometric Reissner-Mindlin shell theory. The isogeometric indirect boundary element method (IBEM) is used to simulate the fluid domain, and the coupling formula is established by connecting the primary variables. IBEM contains information on both sides of the boundary. Naturally, FE-IBE coupling method inherits these attractive features. FE-IBE coupling method has a wide application prospect. In general, it can not only deal with the common problems, but also solve the problems that Finite Element-Direct Boundary Element (FE-DBE) coupling method cannot handle, such as the opened boundary problems, whose inner and outer boundaries contact the liquid. In order to further expand its application range, based on the universality of the primary variables in IBEM, a more generalized coupling formula is derived to solve the hybrid problems with both the closed and opened boundaries. Numerical examples with analytical solution verify the reliability and stability of the proposed IGA FE-IBE coupling method, and two complex problems in aerospace engineering and ocean engineering are studied in detail. Highlights: A NURBS-based isogeometric coupling approach combining IBEM and FEM is presented to solve ASI problems. The FE-IBE coupling method can not only solve the model with opened boundary, but also handle closed problem. The proposed coupling theory is extended to a general case, as well as can dealt with hybrid ASI problems. Two complex problems, i.e. rocket tail and submarine, are studied in detail.